2014
DOI: 10.1039/c3nj01105d
|View full text |Cite
|
Sign up to set email alerts
|

AMVN-initiated expedient synthesis of biaryls by the coupling reaction of unactivated arenes and heteroarenes with aryl iodides

Abstract: The role of radical initiators AMVN and AIBN has been studied in the potassium tert-butoxide mediated biaryl coupling reaction of aryl iodides with unactivated arenes. Radical initiator AMVN promoted carbon-carbon bond formation expeditiously from aryl iodide having various groups such as amino, methoxy, fluoro, methyl, and trifluoromethyl and arenes in the presence of potassium tert-butoxide (4 equiv.) at 110 1C in 2-5 h. Substituted arenes such as toluene, xylene, anisole, and fluorobenzene also proceeded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Furthermore, the AMVN ‐initiated reaction of pyridazine ( 60 ) with 4‐iodotoluene gave 4‐( p‐ tolyl)pyridazine in 68% yield together with a trace amount of the 3‐arylated derivative 41. Notably, the direct arylation of the six‐membered heteroarenes 2 , 3 , 38 , 59 and 60 allowed the efficient cross‐coupling of unactivated arenes with aryl iodides and for the latter reactions spectroscopic evidence suggesting the involvement of radical intermediates was obtained 41…”
Section: Direct (Hetero)arylation Of Heteroarenes With (Hetero)arylmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the AMVN ‐initiated reaction of pyridazine ( 60 ) with 4‐iodotoluene gave 4‐( p‐ tolyl)pyridazine in 68% yield together with a trace amount of the 3‐arylated derivative 41. Notably, the direct arylation of the six‐membered heteroarenes 2 , 3 , 38 , 59 and 60 allowed the efficient cross‐coupling of unactivated arenes with aryl iodides and for the latter reactions spectroscopic evidence suggesting the involvement of radical intermediates was obtained 41…”
Section: Direct (Hetero)arylation Of Heteroarenes With (Hetero)arylmentioning
confidence: 98%
“…A further protocol for the metal‐free direct arylation of pyridine and other six‐membered nitrogen heteroarenes with aryl iodides was recently described by Sanjit Kumar and co‐workers 41. They reported that the radical initiator ( E )‐2,2′‐azobis(2,4‐dimethylvaleronitrile) ( AMVN ) (Figure 7) is able to efficiently promote the direct arylation of pyridine ( 2 ), pyrimidine ( 3 ), 4‐methoxypyridine ( 38 ), 3‐methylpyridine ( 59 ), and pyridazine ( 60 ) with both electron‐neutral and electron‐rich aryl iodides in the presence of KO‐ t‐ Bu at 110 °C.…”
Section: Direct (Hetero)arylation Of Heteroarenes With (Hetero)arylmentioning
confidence: 99%
“…(iii) This clean method afforded compounds 5a – m without the need of additional purification such as column chromatography or recrystallization. (iv) The use of a sealed tube [ 36 43 ] obeys to four out of the twelve green chemistry principles: a cleaner and eco-friendly reaction profile with minimum of waste, solvent without negative environmental impact, shorter reaction time and safely work with a pressure tube canning prevent fires and emissions of hazardous compounds and toxic gas. (v) The reaction described in this work occurred with high atom efficiency (atom economy of 90%) and produced only stoichiometric H 2 O as waste (E-factor of 0.1).…”
Section: Resultsmentioning
confidence: 99%
“…As a pioneering work of biaryl synthesis via radical pathway, in 2008, Itami and colleagues presented a t-BuOK-mediated biaryl coupling of aryl halides and electron-deficient heterocycles involving base-promoted homolytic aromatic substitution (BHAS), in which strong bases acted as a single electron donor to haloarenes, resulting in the generation of aryl radicals. 29) The subsequent works reported that some additives, such as 1,10-phenanthroline, 30,32,40,50) 1,2-dimethylethylenediamine, 31) proline, 37) alcohols, 42,49) p-tolylsulfonyl hydrazide, 44) and urea 51) etc. were effective in the coupling reaction in the presence of an inorganic base (t-BuOK or t-BuONa).…”
Section: Introductionmentioning
confidence: 99%